2011
DOI: 10.1007/s00531-011-0714-7
|View full text |Cite
|
Sign up to set email alerts
|

Lithosphere thermal structure at the eastern margin of the Bohemian Massif: a case petrological and geophysical study of the Niedźwiedź amphibolite massif (SW Poland)

Abstract: The crustal section beneath amphibolite Niedźwiedź Massif (Fore-Sudetic Block in NE Bohemian Massif), modelled on the basis of geological and seismic data, is dominated by gneisses with subordinate granites (upper and middle crust) and melagabbros (lower crust). The geotherm was calculated based on the chemical analyses of the heat-producing elements in the rocks forming the crust and the measurements of their density and heat conductivity. The results were verified by heat flow calculations based on temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…The volume of moving magmas and/or the time of their migration was sufficient to rise temperature of SCLM beneath Księginki (on-rift location) to temperatures 1,060-1,120 °C at depth 35-50 km (Puziewicz et al 2011). The data from off-rift sites generally show temperatures varying between 910 and 1,000 °C (Wilcza Góra and some xenoliths from Krzeniów, Pilchowice, Winna Góra, irrespective of their chemical classification into A or B group), suggesting that temperatures increased during rifting, but were variable at the local Puziewicz et al (2012) speculated the 50 km depth of origin. These temperatures are similar to those characterising the off-rift SCLM at the time of syn-rift volcanism culmination.…”
Section: Thermal Evolution Of the Sclmmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of moving magmas and/or the time of their migration was sufficient to rise temperature of SCLM beneath Księginki (on-rift location) to temperatures 1,060-1,120 °C at depth 35-50 km (Puziewicz et al 2011). The data from off-rift sites generally show temperatures varying between 910 and 1,000 °C (Wilcza Góra and some xenoliths from Krzeniów, Pilchowice, Winna Góra, irrespective of their chemical classification into A or B group), suggesting that temperatures increased during rifting, but were variable at the local Puziewicz et al (2012) speculated the 50 km depth of origin. These temperatures are similar to those characterising the off-rift SCLM at the time of syn-rift volcanism culmination.…”
Section: Thermal Evolution Of the Sclmmentioning
confidence: 99%
“…The much younger xenolith suites from Kozákov in Czech Republic (ca. 4.0 Ma, Šibrava and Havlíček 1980;Ackerman et al 2007) and Lutynia (5.5-3.8 Ma, Birkenmajer et al 2002;Matusiak-Małek et al 2010) represent the cooled mantle lithologies, and conductive geotherms have been proposed for both sites (Christensen et al 2001;Puziewicz et al 2012).…”
Section: Geological Framework Of the Lithospheric Mantle Descriptionmentioning
confidence: 99%
“…According to Wood et al (2013), garnet is stable in fertile peridotites at solidus temperatures at depths greater than c. 85 km. The present-day lithosphere-asthenosphere boundary is located 90-100 km (Puziewicz et al 2012) or c. 100-105 km (Geisler et al 2012) below the SVF, but could have been at c. 70 km at the time when volcanic activity occurred (Puziewicz et al 2015). Considering the geochemical modelling and the geophysical constraints it is likely that the magmas under the SVF originated predominantly in the asthenospheric mantle, close to the base of lithosphere, or in the lowermost lithospheric mantle.…”
Section: Mantle Sources Of Magma Partial Melting Processes and Regiomentioning
confidence: 99%
“…Amphibolites, locally over 3 km thick, occur in the near-surface part, and melagabbros are inferred to form the lower crust. The MOHO is located at a depth of c. 31 km and the lithosphere-asthenosphere boundary at c. 90 km (Puziewicz et al 2012) or 100-105 km (Geissler et al 2012). Recently, Puziewicz et al (2015) suggested that the transition from spinel to garnet peridotite, corresponding to the base of the lithospheric mantle, occurred at a depth of 50-70 km at the time of Cenozoic volcanism.…”
Section: Regional Settingmentioning
confidence: 99%
See 1 more Smart Citation